The Role of Islamic Art in Da'wah Communication Management: A Case Study in Karema Village, Mamuju City - R, Ahmad Wandi .; Abdullah, Nuraeni; Syahrul, Muhammad; Hasriani, Andi; Nengsih, Ratika (Jurnal Economic Resource, 2025)
Study This use method qualitative descriptive with approach studies field . Data sources used in research This are primary data and secondary data . Primary data is taken from community , religious leaders and actors art local and secondary data taken from books , articles as well as search existing references its relevance with research . The method data collection used that is observation , interviews , and documentation . Data management techniques as well as analysis data is done with three stages namely data reduction , data presentation , and withdrawal conclusion . Research result This is development Islamic art in Karema Village has progress , already Lots group Islamic art that was formed like group art Friday Qasidah Blessing Khumairah , group art qasidah Marmatunnajah , group art Al-Ikhlas qasidah , group art Qasidah Babul Jannah, group art Galung-Galung Karema qasidah , group art Qasidah Al-Ikhlas Diponegoro . For group art marawis there are two groups that is group art MTsn 1 Mamuju and MAN 1 Mamuju . Meanwhile For Islamic singer every group art own One or two singers . The role of Islamic art as preaching is also running with good , lots benefits obtained Muslims , including . Making public like listen blessings add faith , Islamic art can tighten connection fellow Muslim in an event, Islamic art can also calm heart and listener can more remembering Allah Subhana Wata'ala , makes many people like it Shalawat and Islamic art are accepted by society